Resection and survival data from a clinical trial of glioblastoma multiforme‐specific IRDye800‐BBN fluorescence‐guided surgery - Kunshan He; Chongwei Chi; Deling Li; Jingjing Zhang; Gang Niu; Fangqiao Lv; Junmei Wang; Wenqiang Che; Liwei Zhang; Nan Ji; Zhaohui Zhu; Jie Tian; et al. (Wiley, 2021)
Abstract Supra‐maximum surgical tumor resection without neurological damage is highly valuable for treatment and prognosis of patients with glioblastoma multiforme (GBM). We developed a GBM‐specific fluorescence probe using IRDye800CW (peak absorption/emission, 778/795 nm) and bombesin (BBN), which (IRDye800‐BBN) targets the gastrin‐releasing peptide receptor, and evaluated the image‐guided resection efficiency, sensitivity, specificity, and survivability. Twenty‐nine patients with newly diagnosed GBM were enrolled. Sixteen hours preoperatively, IRDye800‐BBN (1 mg in 20 ml sterile water) was intravenously administered. A customized fluorescence surgical navigation system was used intraoperatively. Postoperatively, enhanced magnetic resonance images were used to assess the residual tumor volume, calculate the resection extent, and confirm whether complete resection was achieved. Tumor tissues and nonfluorescent brain tissue in adjacent noneloquent boundary areas were harvested and assessed for diagnostic accuracy. Complete resection was achieved in 82.76% of patients. The median extent of resection was 100% (range, 90.6-100%). Eighty‐nine samples were harvested, including 70 fluorescence‐positive and 19 fluorescence‐negative samples. The sensitivity and specificity of IRDye800‐BBN were 94.44% (95% CI, 85.65-98.21%) and 88.24% (95% CI, 62.25-97.94%), respectively. Twenty‐five patients were followed up (median, 13.5 [3.1-36.0] months), and 14 had died. The mean preoperative and immediate and 6‐month postoperative Karnofsky performance scores were 77.9 ± 11.8, 71.3 ± 19.2, and 82.6 ± 14.7, respectively. The median overall and progression‐free survival were 23.1 and 14.1 months, respectively. In conclusion, GBM‐specific fluorescent IRDye800‐BBN can help neurosurgeons identify the tumor boundary with sensitivity and specificity, and may improve survival outcomes.